SUPERVISION OF JOINT STOCK COMPANIES BY THE JORDAN SECURITIES COMMISSION (World Bulletin of Management and Law, 2023)
At the time considered to contribute to the pillars in the stock market companies because they are the main player in the processes that come about within the market, and therefore the success of any financial market depends Ay success of the work of joint stock companies within the market and not to violate the laws and regulations by the companies in order to attract investors and expand the market work and develop and strengthen confidence in the market, and all it depends on is important, but it is onproclaimed joint-stock companies, which control the course of the work of companies and reduce irregularities and this censorship is censorship Securities Commission on jointstock companies